Effect of Compost and Mineral Fertilizers on Development of Mycorphiza in Chir Pine (Pinus roxburghii Sargent) and Patula Pine (P. Patula Schlecht. and Cham) - Ram Reddy, M. A.; Khan, S. N.; Dobriyal, N. D. (Indian Forester, 1976)
The effect of mineral fertilizers and compost of the development of mycorrhiza in chir pine (Pinus roxburghii Sargent), an indigenous slow-growing pine and patula pine (P. patula Schlecht and Cham,) an exotic fast growing pine in India was studied. The effects or fertilizers and compost varied with the plant species, In chir pine, application of compost had better effect of plant growth except for reduction of short roots but application of fertilizers reduced plant growth as well as short roots. On the other hand, addition of compost had no effect on plant growth in patula pine but plant growth increases were directJy proportional to the dosages of NPK fertilizers. Both compost and fertilizers had no effect on short root production. In both the species, mycorrhizal development was retarded by application of compost and high dosages of mineral fertilizers.